Surgical treatment of axillary hyperhidrosis by suction-curettage of sweat glands - Rebeca Maffra de Rezende; Flávio Barbosa Luz (Sociedade Brasileira de Dermatologia, 2014)
Suction curettage is a dermatologic surgery technique for the treatment of axillary hyperhidrosis, which is becoming more popular. Objective: The purpose of this study is to describe the current technique of removal of axillary sweat glands, and evaluate its efficacy and safety. Conclusion: Suction-curettage of sweat glands is a minimally invasive surgical technique that is easy to perform, safe, has high rates of success and relatively few side-effects. It is generally well tolerated by patients and requires shorter time away from daily activities, when compared with other surgical modalities.